Marketing Strategy at Arya Hotel Kadipaten, Majalengka Regency - Ezki Dwi Nugraha; Yelsha Dwi Pasca; Gita Kartika Sari; Mochamad Anjar Albagja (Politeknik Mardira Indonesia, 2025)
This research is motivated by the importance of SWOT analysis in marketing strategy with 7P marketing mix. The method used in this study is SWOT analysis with interviews to evaluate marketing strategies at Arya Hotel Kadipaten, Majalengka Regency. The results of the study with the SWOT, IFAS and EFAS analysis matrices show that with the S-O strategy, namely by using strengths to gain opportunities, the Company uses the S- O strategy, namely 1) improving complete and modern hotel facilities: taking advantage of the increasing number of tourists on a national and international scale, thereby increasing market share. 2) utilizing partnerships with trusted online booking providers; increasing the number of users of online travel agent applications (traveloka & tiket.com) to attract new consumers.